2015
DOI: 10.1111/jan.12847
|View full text |Cite
|
Sign up to set email alerts
|

Nursing performance under high workload: a diary study on the moderating role of selection, optimization and compensation strategies

Abstract: The use of selective optimization with compensation is conducive to nurses' job performance under high workload levels. This finding is in line with calls to empower nurses' individual decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 69 publications
3
51
1
3
Order By: Relevance
“…These feelings could affect not only the individual nurse but also the whole team [44, 50]. A study investigating nursing performance under high workload revealed that certain mechanisms such as selection, optimization and compensation strategies (SOC model) support nurses’ individual decision-making and ability to perform well [9]. The SOC model implicates that nurses use their individual resources more efficiently and adaptively by setting priorities and focus on fewer but most relevant goals, pursue these goals in an optimized way and flexibly apply compensatory means [10].…”
Section: Discussionmentioning
confidence: 99%
“…These feelings could affect not only the individual nurse but also the whole team [44, 50]. A study investigating nursing performance under high workload revealed that certain mechanisms such as selection, optimization and compensation strategies (SOC model) support nurses’ individual decision-making and ability to perform well [9]. The SOC model implicates that nurses use their individual resources more efficiently and adaptively by setting priorities and focus on fewer but most relevant goals, pursue these goals in an optimized way and flexibly apply compensatory means [10].…”
Section: Discussionmentioning
confidence: 99%
“…O aktualności ww. tematyki natomiast świadczą publikacje dotyczące wydajności pracy pielęgniarek zamieszczone na serwerach internetowych w latach 2015 i 2016 [6,7].…”
Section: Wprowadzenieunclassified
“…O aktualności ww. tematyki natomiast świadczą publikacje dotyczące wydajności pracy pielęgniarek zamieszczone na serwerach internetowych w latach 2015 i 2016 [6,7].Tematyka wydajności pracy stanowiła obiekt zainteresowań wielu badaczy. J.P. Cambell definiuje wydajność pracy, jako zachowania i działania istotne dla realizacji celów organizacji [8].…”
unclassified
“…However, MWL literature has mainly been centered on measuring performance by means of operative tasks, like those related to traffic or transport research, real flight, flight simulation, air traffic control, peripheral detection, or formal memory/follow-up tasks (see Bowling & Kirkendall, 2012;Brookhuis & Waard, 2002;Hart, 2006;and Young et al, 2015). In this sense, only a few and very recent works have focused on relating MWL and one of the key concepts in skilled work settings: decision-making (Byrne, 2013;Baethge, Müller, & Rigotti, 2016;Jackson, Kleitman, & Aidman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to clinical decisionmaking, Byrne (2013) has suggested-on the basis of the existing research-that MWL and complexity of the information may be key factors to determine which kind of clinical decision-making is developed: schemata-based methods or conscious metacognition procedures. Baethge et al (2016) have shown empirically that the influence of MWL on performance quality is moderated by the way in which selection, optimization, and compensation of resources and goals are handled by nurses. Jackson et al (2014), using driving simulation strategies, have provided support for the existence of a MWL zone of optimal DM performance, below or above which a worse quality of DM is produced, as has been suggested for the relationship between MWL and other classical performance measures.…”
Section: Introductionmentioning
confidence: 99%